Telomere length distribution in blood and saliva by RT-PCR in age-varying Thais: A Pilot Study - Charoenying, Thanvisith; Kruanamkam, Wantika; Yu-iam, Songwut; U-chuvadhana, Pisanu; Rerksngarm, Thaval (วารสารวิทยาศาสตร์สุขภาพ มหาวิทยาลัยปทุมธานี, 2020)
The old-age populations are increasing in number in virtually every country. Identifying reliable biological indicators of virtual aging is a key objective in geroscience. Telomeres, the DNA–protein structures located at the ends of chromosomes, have been convincingly proposed a biomarker of aging. Epidemiologic studies show an association between telomere length (TL) in leukocyte and aging. This study investigated TL in blood leukocytes and cells in saliva samples of 108 healthy Thai population at various age ranges. Subjects were divided into four groups (I:21-40 years, II:41-60 years, III:61-80 years and IV:80 years up), The extracted DNA was analysed for TL by qPCR. The mean length of the telomere were found statistically significant different among age groups and decrease with increasing age (p-value < 0.05) in both blood and saliva samples. The means of TL in I, II, III, and IV in blood were 1.03±0.016, 0.92±0.022, 0.82±0.028, and 0.56±0.100, respectively; whereas in saliva were 1.07±0.021, 0.95±0.022, 0.82±0.028, and 0.59±0.040, respectively. In addition, the relationship of TL in blood and saliva was R = 0.418, p-value = 0.00. The preliminary results demonstrated consistent telomere length measurements in saliva as an alternative peripheral source compared to blood. Saliva could be considered as a non-invasive and as a reliable source of DNA for measuring telomere length